LEWIS CAPALDI’S SOMEONE YOU LOVED: A READER RESPONSE ANALYSIS OF THE LYRIC - Amelia, Dina; Rahayu, Indah (Linguistics and Literature Journal, 2025)
This research analyzes Lewis Capaldi’s song Someone You Loved using Reader-Response Theory. The study focuses on how listeners give meaning to the song lyrics based on their personal feelings and experiences. Reader-Response Theory, especially Louise Rosenblatt’s transactional approach, explains that meaning is not fixed in the text but created through interaction between the text and the reader. The researcher used a qualitative descriptive method and collected data through a Google Form questionnaire based on seven reader-response strategies from Beach and Marshall (1991): describing, engaging, conceiving, explaining, connecting, interpreting, and judging. Twenty respondents from different countries shared their emotional and personal reactions after listening to the song. The findings show that most listeners interpreted the song as a story about love, loss, and emotional healing. Each listener’s background and experience influenced how they understood the song’s message. This study proves that song lyrics can be studied as modern literature and that listeners play an active role in creating meaning from popular music. Keywords: Lewis Capaldi, reader-response theory, Someone You Loved, song lyrics, qualitative research